Jesuit Schools and Missions in the Orient - Manso, Maria de Deus (2012)
On 27th February 1540, the Papal Bull Regimini Militantis Eclesiae estabilished the oficial institution of The Society of Jesus, centred on Ignacio de Layola. Its creation marked the begining of a new Order that would accomplish its apostolic mission through education and evangelisation. The Society´s first apostolic activity was in service of the Portuguese Crown. Thus, Jesuits became involdev within the missionary structure of the Portuguese Patronage and ended up preaching massively across non-European spaces and societies.